A Two-Step Procedure to Estimate Participation and Premiums in Multistate Health Plans - Cordova, Amado (RAND Corporation, 2013)
Multistate plans (MSPs) provide an attractive alternative among the health insurance plans established by the Affordable Care Act because they will have to be offered in multiple states. In this study, the authors' objectives were to identify and characterize population groups that would likely be interested in enrolling in MSPs and to develop a methodology to project participation and estimate premiums for these plans.